2009
DOI: 10.1080/14756360802051362
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents isolated from Polygala japonica leaves and their inhibitory effect on nitric oxide production in vitro

Abstract: A methanolic extract of dried leaves of Polygala japonica Houtt (Polygalaceae) significantly attenuated nitric oxide production in lipopolysaccharide-simulated BV2 microglia. Five anthraquinones chrysophanol (1), emodin (2), aloe-emodin (3), emodin 8-O-b-D-glucopyranoside (4) and trihydroxy anthraquinone (5), and four flavonoids kaempferol (6), chrysoeriol (7), kaempferol 3-gentiobioside (8) and isorhamnetin (9) were isolated from the methanolic extract using bioactivity-guided fractionation. Among them, compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Though the antioxidant activity of kaempferol derivatives on DPPH radical scavenging assay was moderate, they were reported to have inhibitory activities on lipopolysaccharide-induced nitric oxide production in BV2 microglia (Kim, Jang, Lee, Sung, & Kim, 2009), CB 1-6 V and HSV-1 virus infection (Yao & Wang, 1999), and protein kinase CK 2 in vitro and in HL-60 cells (Lin, Liu, Chen, & Liang, 2006). Glycosylated kaempferol derivatives were also reported from some vegetables and fruits, e.g.…”
Section: Dpph Radical Scavenging Capacitymentioning
confidence: 97%
“…Though the antioxidant activity of kaempferol derivatives on DPPH radical scavenging assay was moderate, they were reported to have inhibitory activities on lipopolysaccharide-induced nitric oxide production in BV2 microglia (Kim, Jang, Lee, Sung, & Kim, 2009), CB 1-6 V and HSV-1 virus infection (Yao & Wang, 1999), and protein kinase CK 2 in vitro and in HL-60 cells (Lin, Liu, Chen, & Liang, 2006). Glycosylated kaempferol derivatives were also reported from some vegetables and fruits, e.g.…”
Section: Dpph Radical Scavenging Capacitymentioning
confidence: 97%
“…(Du et al, 2013;Kim et al, 2009;Wang et al, 2007;Xiang et al, 2005). In the present study, it was found that compounds C1 and C2 could significantly reverse decreased expression of a7 and a3 nAChRs and C2 also could significantly increase expression of SPY in Ab 1-42 -induced SH-SY5Y cells, which indicating that compounds C1 and C2 effectively have protective roles against Ab-induced neurotoxicity.…”
Section: Identification Of Permeable Componentsmentioning
confidence: 50%
“…Triterpenoid saponins from the roots of P. japonica Houtt. have anti-inflammatory activity through inhibition of nitrite and PGE 2 production, iNOS and, COX-2 protein expression and TNF-α, IL-1β, IL-6, and IL-12 mRNA expression in LPS-stimulated BV2 cells (Kim et al 2009;Ahn et al 2005). Previous research has reported that PSF inhibit the secretion of inflammatory cytokines induced by LPS and its mechanism is associated with the NF-κB signaling pathway (Wei et al 2014;Yan et al 2015), but the effect and mechanism vary in different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Polygala japonica Houtt (Gua-zi-jin in Chinese) is used in traditional medicine for the treatment of various inflammatory disorders such as acute tonsillitis, pharyngitis and pulmonitis (Wang et al, 2008). Previous studies have reported triterpenoid saponins from P. japonica exhibited the anti-inflammatory activities on carageenan-induced mouse paw edema and nitric oxide (NO) production in LPSstimulated RAW264.7 macrophages (Wang et al 2008;Kou et al 2006;Kim et al 2009). Triterpenoid saponins from the roots of P. japonica Houtt.…”
Section: Discussionmentioning
confidence: 99%